Magnitude of Anemia and Undernutrition Among Primary School Children in a Setting of Mass Deworming in Central Ethiopia - Wordofa M; Abera D; Mesfin A; Desta K; Taye B; Tsegaye A (Dove Medical Press, 2022)
Moges Wordofa,1 Dessie Abera,1 Abiyot Mesfin,2 Kassu Desta,1 Bineyam Taye,3 Aster Tsegaye1 1Addis Ababa University, College of Health Sciences, Department of Medical Laboratory Sciences, Addis Ababa, Ethiopia; 2Pyramid Pharma Plc, Addis Ababa, Ethiopia; 3Biology Department, Colgate University, Hamilton, NY, USACorrespondence: Moges Wordofa, Addis Ababa University, College of Health Sciences, Department of Medical Laboratory Sciences, Addis Ababa, Ethiopia, Email heranmakmow@gmail.comBackground: Undernutrition and anemia in children continue to be a public health problem in developing countries. Besides, intestinal parasitic infection among school children is common in developing countries. World Health Organization (WHO) recommends periodic deworming of children who live in endemic areas. The aim of this study was to determine the magnitude of anemia and undernutrition among school children in a setting of mass deworming.Methods: A cross-sectional study was conducted among 510 school children aged 5- 14 years from three randomly selected governmental schools in Sululta town, central Ethiopia. Socio-demographic variables were assessed using interviewer administered structured questionnaire. Anthropometric data were obtained and analyzed using WHO Anthroplusv1.0.4. Venous blood samples were collected using EDTA vacutainers. Hemoglobin level was determined by Sysmex KX-21N automated hematology analyzer and stool samples were processed using direct wet mount, formol-ether concentration and Kato-Katz methods. Data were entered and analyzed using SPSS version 21. Logistic regression analysis was performed to determine the association of anemia and undernutrition with the independent variables.Results: The overall magnitude of anemia was 3.7%. Among anemic individuals, 84.2% and 15.8% of participants had mild and moderate anemia, respectively. The magnitude of stunting and thinness was 16.9% and 10.8%, respectively. Of them, 18.6% of stunting and 14.5% of thinness were severe. Of factors related to undernutrition, children from large families (≥ 5) were less likely to be stunted (AOR=0.38, 95% CI=0.2- 0.7, P=0.002) compared to small families.Conclusion: The magnitude of anemia in the study area was considered as an insignificant public health problem and none of the socio-demographic variables of participants were significantly associated with anemia and likewise with undernutrition except for family size. Further studies are required to clearly understand the impact of mass deworming on the magnitude of anemia and undernutrition.Keywords: anemia, undernutrition, deworming, school children